Sustainable Professional Development and Learning Quality of Elementary School Teachers - Sukmaratri, Wiganingtyas; Murwaningsih, Tri; Yulisetiani, Septi (Universitas Sebelas Maret, 2026)
This study aims to analyze the relationship between Continuous Professional Development (CPD) and the quality of elementary school teaching in the Ki Hajar Dewantoro Cluster, Wonogiri. CPD focuses on training programs and Teacher Working Groups (KKG). A quantitative method with a cross-sectional correlational design was employed. The sample consisted of 58 teachers from six schools selected through total sampling. Instruments included questionnaires on training participation, KKG engagement, and teaching quality adapted from standardized measures. Data were analyzed using Pearson correlation. The results indicate a significant positive correlation between training participation and teaching quality (r = 0.42; p < 0.01), while KKG engagement shows a stronger correlation (r = 0.58; p < 0.01). These findings highlight the importance of strengthening training programs and KKG activities as key strategies to improve the quality of elementary school teaching.